Employability versus integral education: integrated high school in the state of Ceara - José Deribaldo Gomes dos Santos; Ellen Cristine dos Santos Ribeiro; Rosiane Bento Barros (Universidade Federal de Santa Catarina, 2018)
This paper uses Marxist theory to analyze if the integrated education contained in the proposal for Integrated High School Education in Ceará state is truly contemplated. The relevance of this issue is confirmed by the investigative effort to reveal the essence of basic intentions of public policy for vocational education, considering the shortage of bibliographic production about this issue. The methodology included interviews with 79 students at a high school in the public state system, EEEP [1] Cavalcante Maria Costa, which is the center of the implementation of this project. The purpose of the study is to help broaden the critical understanding of this project in students' education and the socio-economic development of Ceará. The research shows that policies aimed at educating workers follow a business logic and are linked to capital in deep crisis, thus constituting a real hindrance to the integral education defended by Marxist classics.